Learning expectations, challenges, and strategies of university students on English-medium instruction - Syariful Muttaqin; Hsueh-Hua Chuang (Journal on English as a Foreign Language, 2022)
Despite its wide application at tertiary education, English-medium instruction (EMI) poses complexities in practices. This study investigated EMI students